2005
DOI: 10.1080/10810730590934262
|View full text |Cite
|
Sign up to set email alerts
|

Examining College Students' Intentions to Become Organ Donors

Abstract: 502 university students completed survey items on attitudes, experiences, knowledge, and behaviors related to organ and tissue donation (OTD). Despite positive attitudes toward organ donation, only 11% of students formally have declared their intentions to donate through the state registry or by signing an organ card. When asked to report why they have not signed an organ donor card/registry, students reported, "not considering the topic," "intentions to donate in the future," and "general negative attitudes" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 31 publications
5
86
0
4
Order By: Relevance
“…Noteworthy is the lack of a relationship between the perception of health care in Spain and the will to donate, present in many studies (9,13,14,23), although it seems clearly conditioned by the scarce representation of the layers of negative ratings. However, and with regard to the informative variables, the will to donate in the immigrant population also varies as a function of diverse aspects of the available information on the topic, underscoring the perception of efficacy, direct knowledge, and the existence of qualified information as the elements most closely linked to a positive disposition, and also following the general tendencies previously found in this field (20,40,(49)(50)(51). The results obtained through multivariate analysis reinforce the evidence of the predictive power of religious beliefs on the disposition to donate and define differentiated groups that are somewhat homogeneous internally in this aspect, grouping the beliefs that already appeared as the most reluctant in the bivariate analysis (practicing Muslims, Buddhists, and Jews).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy is the lack of a relationship between the perception of health care in Spain and the will to donate, present in many studies (9,13,14,23), although it seems clearly conditioned by the scarce representation of the layers of negative ratings. However, and with regard to the informative variables, the will to donate in the immigrant population also varies as a function of diverse aspects of the available information on the topic, underscoring the perception of efficacy, direct knowledge, and the existence of qualified information as the elements most closely linked to a positive disposition, and also following the general tendencies previously found in this field (20,40,(49)(50)(51). The results obtained through multivariate analysis reinforce the evidence of the predictive power of religious beliefs on the disposition to donate and define differentiated groups that are somewhat homogeneous internally in this aspect, grouping the beliefs that already appeared as the most reluctant in the bivariate analysis (practicing Muslims, Buddhists, and Jews).…”
Section: Discussionmentioning
confidence: 99%
“…In search of solutions, research on organ donation has explored individual differences between potential donors and nondonors, including age (Siminoff, Gordon, Hewlett, & Arnold, 2001), altruism (Morgan & Miller, 2002a), ethnicity (Morgan, 2004;Morgan, Miller, & Arasaratnam, 2003), knowledge (Feeley & Servoss, 2005;Weber et al, 2006), normative 138 QUICK, KIM, AND MEYER influences (Morgan & Miller, 2002b), and sex (Thompson, Robinson, & Kenny, 2003) on outcome variables such as attitudes, willingness to communicate about organ donation, and intentions of becoming a potential donor. In addition, research has studied health campaigns designed to raise awareness about organ donation (Morgan, Miller, Arasaratnam, 2002;Weber et al, 2006), the persuasiveness of certain message features (Feeley, Marshall, & Reinhart, 2006;Kopfman, Smith, Morrison, Massi, & Yoo, 2002), and media portrayals of organ donation (Feeley & Vincent, 2007;Morgan, Harrison, Chewning, DiCorcia, & Davis, 2007;Quick et al, 2007).…”
mentioning
confidence: 99%
“…Additionally, researchers have posited that one difference between non-signers who hold positive attitudes toward organ donation and those people who have already signed an organ donor card is that non-signers tend to be missing some vital piece of knowledge. As a result of this perceived knowledge deficiency, Feeley and Servoss (2005) suggested that ''campaigns should include education and information on the procurement process while dispelling popular and media-induced myths on the topic'' (p. 244).…”
Section: The Campus Organ Donor Projectmentioning
confidence: 98%